Long term prognosis of atrial fibrillation in ST-elevation myocardial infarction patients undergoing percutaneous coronary intervention. (1st August 2017) - Topaz, Guy; Flint, Nir; Steinvil, Arie; Finkelstein, Arik; Banai, Shmuel; Keren, Gad; Shacham, Yacov; Yankelson, Lior
Abstract: Background: Atrial fibrillation (AF) is a well-known complication in the setting of ST elevation myocardial infarction (STEMI). Data on the long-term prognostic implications of New-Onset AF (NOAF) complicating STEMI in the era of complete revascularization remains controversial. Our aim therefore was to evaluate the long-term prognosis of prior AF (pAF) and new-onset AF (NOAF) in STEMI patients undergoing percutaneous coronary intervention (PCI). Methods: We studied 1657 consecutive STEMI patients hospitalized in the cardiac intensive care unit during 2008–2014. We reviewed patient records for the occurrence of pAF and NOAF. NOAF was defined as AF occurring within 30 days of the STEMI episode. Patients were followed for a mean period of 3.4 ± 2.1 years. Results: Within our cohort 77 (4.6%) patients had pAF and 47 (2.8%) had NOAF. Patients with any AF were older and had a reduced systolic ejection fraction. Thirty-day mortality and all-cause mortality rates were significantly higher in patients with pAF in comparison to those without AF (9.1% vs. 2.2% p  < 0.001 and 31.2% vs. 9.4%, p  < 0.001, respectively). NOAF showed a trend for increased all-cause mortality (17% vs. 9.1%, p  = 0.07) and 30-days mortality (6.4% vs. 2.1%. p  = 0.09). In a multivariate regression model, pAF but not NOAF was a predictor of mortality throughout the follow-up period (HR 2.02, 95% CI 1.2 to 3.1, p  = 0.005 and HR 1.1, 95% CI 0.56 to 2.2, p  = 0.75, respectively). Conclusions: Prior AF and not new-onset AF is an independent predictor of both short and long term mortality in patients treated with PCI.